MARKETING COMMUNICATION STRATEGY TO INCREASE THE NUMBER OF VIEWERS THROUGH EXTENSION THE TARGET MARKET - Rani, Cinthya Kusuma; Natakoesoemah, Susilowati (INFOKUM, 2022)
The increase in the number of television stations, both national and local, from year to year followed by an increase in broadcast quality and quantity, is evidence of the development of television broadcasting media. Competition between television stations in Indonesia is not only in its function as a medium for delivering entertainment, but also in its function as a medium for delivering information or news. First established in 2015, CNN Indonesia is classified as a new media category and requires an extra strategy to introduce and attract viewers. At the beginning of its appearance, CNN Indonesia did not have as many viewers as it does now. The problem of the lack of number of viewers made CNN Indonesia implement a simulcast program strategy. This simulcast program is a means used to extension the number of CNN Indonesia's market to increase the number of viewers. With the big names of several media owned by Trans Media, several CNN Indonesia TV programs are broadcast on Trans TV, with this simulcast program strategy, the programs being watched on CNN Indonesia TV channel, they can also be watched on Trans TV. The target audience for news TV will certainly be different from other TV stations, such as entertainment TV. This study used a qualitative research approach with case study method using in-depth interviews three informant from CNN Indonessia TV and data from Research & Development Departement CNN Indonesia TV. This thesis uses media convergence theory, omnichannel marketing concept and target market expansion. The result of this research is, through the simulcast program, CNN Indonesia TV finally expands its target market by adding Trans TV viewers. This strategy has proven to be able to overcome the problems experienced by CNN Indonesia TV as a newcomer to get an increase in the number of viewers with simulcast programs on Trans TV. With the differences in characters between Trans TV viewers and CNN Indonesia TV, CNN Indonesia TV in the simulcast program must be modified and repackaged to match the content.